(untitled) (Engineering and Sustainability Journal, 2026)
Marine Spatial Planning (MSP) is a strategic instrument for integrated ocean governance, particularly in contexts of increasing pressure on marine resources and multiple maritime uses. This study evaluates the institutional and legal challenges of MSP in Angola, within the Benguela Current System, focusing on the national legal framework and comparative regional governance. The analysis was based on official documents, legislation, and public policies, addressing sectors such as environment, fisheries, oil and gas, defence, and spatial planning. Results indicate that Angola’s legal framework remains strongly sector-based, prioritising resource exploitation and licensing, with limited incorporation of sustainability principles, ecosystem-based approaches, and integrated spatial planning. High institutional fragmentation was observed, reflected in overlapping mandates among ministries and public agencies, undermining intersectoral coordination and MSP implementation. Land–sea integration also showed weaknesses, particularly in coastal areas, limiting the management of ecological and socio-economic systems. Comparison with Namibia and South Africa demonstrates that dedicated legislation, clear institutional structures, and consolidated coordination mechanisms facilitate effective MSP implementation. The study concludes that strengthening MSP in Angola requires a framework law, enhanced interministerial coordination, integration between terrestrial and marine planning instruments, and systematic adoption of regional best practices within the Benguela Current Commission context